Influence of Taxation Administration Modernisation, Taxation Knowledge and Quality of Tax Consultant Serviceson The Compliance of Taxpayers in Reporting The Badan Annual Notice Surat (SPT) at KKP Pratama Bandung Cicadas 2022 - Mustari, Ghinda; Kasir, Kasir (Dinasti International Journal of Management Science, 2024)
This study aims to determine how the modernization of tax administration, tax knowledge, and the Quality Of Tax Consultant Services affect taxpayer compliance in reporting Corporate SPT at KPP Pratama Bandung Cicadas. The research method used is a quantitative method with a verification approach. verification approach is applied to explore the relationship between variables and test hypotheses that suspect a relationship between these variables. The results of the study explain that Modernization of Tax Administration, Tax Knowledge, Quality Of Tax Consultant Services together have an impact of 93.90% on taxpayer compliance. The remaining 6.10% is influenced by other factors not examined